Sosialisasi Child Grooming : Cyber Crime yang Mengintai Anak-Anak di Era Digital - Fitri Hardianti; Wahyudi Kumorotomo; Widodo Agus Setianto (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
Indonesia is in second place in cyber crime cases in the world. According to Komnas Perempuan’s record, in 2022, online gender-based violence (KBGO) cases occupy the highest position in complains to Komnas Perempuan in the public domain, covering 69% of the total cases. Riau, as one of the provinces in Indonesia, is also not immune to cases of sexual crimes in cyber space. A number of online media reported that Riau experienced an increase in cases of violence against children and women in 2021, this was an increase of 40 cases compared to 2020 . One of the reasons is the lack of parental knowledge of sexual crimes. In addition, the public’s view of sex is still considered very taboo. With current technological developments, it is analogous to an “open gate” that everything can be easily accessed and all forms of cyber crime will easily stalk children, including child grooming. The purpose of this community service is to socialize to the community regarding the dangers of child grooming and provid solutions on how to overcome them. This community service will involve one partner, namely the Raudathul Athfal Alkausar school, Sialang Sakti Village, Dayun District, Siak Regency. The solution offered in this service is to provide counseling related to one type of sexual crime in the digital era called Grooming to both teachers and parents. One of the successes in this service can be seen from the understanding obtained by the teachers and also the guardians of the students. The output targets of this service will later be published in the nationally accredited journal and local electronic mass media.